Credit Risk of FX Loans in Poland. Interest and FX Rate Dependence - Wośko, Zuzanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
One of important financial stability risks in Poland is relatively high share of bank loans denominated in foreign currency extended to unhedged borrowers. Banks engaged in FX lending are exposed to indirect exchange rate risk (as a component of credit risk) through currency mismatches on their clients’ balance sheets. A significant depreciation of Polish zloty would translate into an increase of value of outstanding debt (also in relation to the value of collateral) as well as in the flow of payments to service the debt. As a result, the debt-servicing capacity of unhedged domestic borrowers would deteriorate, leading to a worsening the financial condition of the private sector. The reduction of borrower’s ability to service the loan and lower recovery rate affects the loan portfolio quality, increases banks’ loan losses. This effect can be mitigated or intensified by foreign interest rates of extended FX loans (i.e. LIBOR). The borrower’s ability to service such loan depends strongly on FX rate but also on monetary authorities from abroad. Therefore both risks are linked and should be considered together. This paper presents the statistical analysis of the dependence of foreign interest rates and FX rate of Polish zloty using measures of dependence, amongst others, copula function approach.